2015
DOI: 10.4103/0972-124x.156882
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease status and associated risk factors in patients attending a Dental Teaching Hospital in Rawalpindi, Pakistan

Abstract: Background:Investigators have identified an association of socio-demographic and medical factors with periodontal risk. This study observed status and association of periodontal disease and associated risk factors/indictors.Materials and Methods:All patients attending a dental teaching hospital were interviewed for socio-demographic and medical information through a structured questionnaire. Participants were examined for periodontal status using the community periodontal index (CPI), by a single examiner duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
4
45
3
Order By: Relevance
“…A study in Pakistan (2015) among those aged 20–60 years found a similar prevalence of periodontitis of 34.5%, another in Bangladesh (1990) found a prevalence of 42%, while a study among urban residents of Brazil (2004) showed a prevalence of 79% of clinical attachment loss. [ 17 18 19 ] Studies done in developed countries such as the United States and Canada showed a prevalence of 47% and 67.8%, while a study in France among those aged 35–64 years showed a higher prevalence of 82.23%. [ 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Pakistan (2015) among those aged 20–60 years found a similar prevalence of periodontitis of 34.5%, another in Bangladesh (1990) found a prevalence of 42%, while a study among urban residents of Brazil (2004) showed a prevalence of 79% of clinical attachment loss. [ 17 18 19 ] Studies done in developed countries such as the United States and Canada showed a prevalence of 47% and 67.8%, while a study in France among those aged 35–64 years showed a higher prevalence of 82.23%. [ 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was also found to be associated with chronic periodontitis in this study, similar to the results from previous studies, indicating the need to target this modifiable risk factor for promoting oral health. [ 18 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…8 In Asian countries, its prevalence is reported to be as high as 15 to 20% 9 and in Pakistan, the prevalence of severe periodontitis is calculated up to 34.1%. 10 Human saliva is composed of salivary grand secretions (major/minor), immunoglobulins, peptidases, mucins, hormones, DNA or RNA molecules, and a variety of electrolytes that reflect changes in the physiological and pathological states of the human body. Therefore, saliva is considered as the "mirror" of the body.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic periodontitis varies according to different geographic regions and is seen to be the highest in Asian countries (about 15%-20%) [7]. In Pakistan, the prevalence of chronic periodontitis is reported to be 31.4% [8].…”
Section: Introductionmentioning
confidence: 99%